Effect of Patient Follow-Up System on the Treatment Compliance of Osteoporotic Patients and on Quality of Life - Ercan Madenci; Erhan İbas; İrfan Koca; Özlem Altındağ (Galenos Yayinevi, 2014)
Objective: Osteoporosis is a chronic disease that can take a long time to treat and is an important public health issue since it increases the risk of fractures and it has negative effects on quality of life with its social, psychological, economic and physical dimensions. It was aimed to evaluate the effect of patient follow-up program on drug compliance and quality of life. Materials and Methods: This study included 233 patients diagnosed with osteoporosis and the study was continued with 200 patients (173 females with postmenopausal osteoporosis, 27 males with senile osteoporosis). Patients were divided into 3 groups as daily, weekly and monthly follow-up groups. Patients were called by telephone with the help of patient follow-up program. Monthly Medication Possession Ratio (MPR) was calculated. Qualeffo-41 quality of life data were assessed at baseline, at the 3rd and 6th months. Results: From the baseline within 6 months, MPR levels were significantly increased in all groups (p<0.05). Monthly follow-up group was found the most compatible group compared to others. Significant changes in quality of life were observed (p<0.05). Conclusions: Dose intervals, especially long dose interval regimens and patient drug reminder programs are highly effective on compliance and quality of life would be better as the compliance increases. It should be bear in mind that if treatment incompliance occurs it may lead to medical harms and economical losses. (Turkish Journal of Osteoporosis 2014;20: 46-50)